Green function of a parabolic boundary-value problem and the optimization problem - Pukalskyi, I. D. (Ukrains’kyi Matematychnyi Zhurnal, 2000)
We establish necessary and sufficient conditions for the choice of optimal control over systems de-scribed by a general parabolic problem with restricted internal control.